La diversidad de especies de vivientes corpóreos a la luz de la filosofía de Santo Tomás de Aquino - Pavez, Carreño (Sapientia, 2017)
Beyond the theories and ideologies that sometimes are presented as inevitably linked to it, the truth is that the fact of evolution of living species is a highly relevant theoretical framework in modern biology. Therefore, any attempt to establish a fruitful dialogue between biology and Thomistic philosophy must address this issue; in order to advance in that direction, however, one should answer first the question about the diversity of species of living beings, a controversial topic among Thomistic scholars. In this article we argue that the multiplicity of biological species is compatible and consistent with the metaphysical scheme proposed by Thomas Aquinas; moreover, we think that this thesis was suggested by Aquinas himself in some passages of his work, though certainly not in an evolutionary context. As Saint Thomas repeatedly points out, in most cases we do not know the specific difference included in the definition of these species. This, however, does not imply our absolute ignorance about them; we think, on the contrary, that the philosophical examination of vital operations may constitute a valid strategy for advancing, at least partially, in the distinction of certain species of corporeal living beings. In the final section of the article we apply this principle in the philosophical analysis of the criterion of interbreeding that biologists commonly use to develop their taxonomic classifications.